2015
DOI: 10.1007/s00464-015-4361-0
|View full text |Cite
|
Sign up to set email alerts
|

Acuity, outcomes, and trends in the transfer of surgical patients: a national study

Abstract: Patients transferred for surgery represent a higher acuity population than non-transferred patients, and the number of transfers continues to rise. Even when matched by comorbidities, transferred patients have worse outcomes. Surgical sub-specialization and physician tiering may complicate future transfer practices. Efficient transfers, effective physician communication, and ready availability of medical records are critical in improving patient transfers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 36 publications
3
27
0
Order By: Relevance
“…Evaluation of national patient databases indicate an increase in the proportion of interhospital transfers among EGS admissions in the United States by 150% between 2002 and 2011. 2 , 6 This practice burdens patients, who must travel long distances to obtain health care, as well as tertiary referral centers, who often suffer financially from caring for transferred patients. 10 Our study is the first to prospectively delineate circumstances prompting transfer to tertiary centers for EGS diagnoses.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Evaluation of national patient databases indicate an increase in the proportion of interhospital transfers among EGS admissions in the United States by 150% between 2002 and 2011. 2 , 6 This practice burdens patients, who must travel long distances to obtain health care, as well as tertiary referral centers, who often suffer financially from caring for transferred patients. 10 Our study is the first to prospectively delineate circumstances prompting transfer to tertiary centers for EGS diagnoses.…”
Section: Discussionmentioning
confidence: 99%
“… 10 , 11 , 12 Transfer patients generally have higher rates of comorbidities and a higher level of acuity, resulting in worse mortality and increased length of stay, compared to their directly admitted counterparts. 2 , 5 , 6 , 13 , 14 As a result, tertiary referral centers oftentimes suffer a net financial loss in caring for these patients, particularly in the setting of value-based reimbursement models. 10 Additionally, transfers over significant distances burden patients and their families during both the inpatient stay, as well as during the follow-up period.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inter‐hospital transfers are time‐consuming, complex and expensive. Preoperative inter‐hospital transfer in general surgical patients delays surgical intervention and these patients have worse outcomes, even when matched per operation and comorbidities . There has been a trend towards centralization of surgical services, however, this is often not appropriate in the setting of emergency surgery where delay to surgical intervention may be fatal .…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6][7][8][9][10] Limited studies in surgical patients have shown similar trends. [11][12][13][14][15] No prior studies examining interhospital transfer for conditions treated by otolaryngologists have been performed.…”
mentioning
confidence: 99%